Impact of the Accounting Environment on the Preparation of Financial Reports in Commercial Banks - Naeem Bachi, Adheem; Makki Rashid, Arshed; Yas Khudhair, Shaymaa (International Journal of Supply Chain Management, 2019)
Due to the wide scope of the accounting environment, the purpose of this study is to explain a number of components of the accounting environment and their impact on the financial reporting of commercial banks. The components (liquidity, financial leverage, profitability, profit management, company size, company life cycle, corporate governance) are randomly selected from the background of the research and each research record is presented. Considering the aim of this study is to investigate the relationship between the two main variables of the research 1- accounting environment (independent variable) 2- preparing financial reports of commercial banks (dependent variable). Therefore, descriptive - correlation method has been used. Also, the library method has been used to collect the content related to theoretical foundations and research background. The statistical population of the study is 40 branches of commercial banks located in Australia. In this research, randomly, 7 variables were selected from the research background that were components of the accounting environment and then a researcher-made questionnaire with appropriate validity and reliability of about 0.1 was obtained by the research participants. After reviewing the collected data, we have tried to apply the multivariate regression test in SPSS software. Regression results showed that two independent variables (profit management, company life cycle) have a positive and significant relationship with the dependent variable (financial reporting of commercial banks) in the present research. Earnings_manage variable with 0.048 is smaller than 0.05 and shows that there is a significant relationship between this independent variable and the dependent variable (financial reporting of commercial banks). Also, Reg_date_on_s_exchange variable with a correlation coefficient of 0.000 is less than 0.05, indicating that there is a significant relationship between this independent variable and the dependent variable (financial reporting of commercial banks). Other variables such as financial leverage, liquidity, etc. have not shown any significant relationship.